Strategic human resources management and hotel performance - Machado,Luciano Aparecido Nascimento (2019)
This study aims to verify the influence of Strategic Human Resources Management in hotel performance, analysing hotels located in Greater Florianópolis, Brazil. The study conducted bibliographical research, presenting a theoretical basis to support the discussion, and, in terms of methodology, adopted a descriptive (in the positivist paradigm) approach. The study proposed a model analysed by exploratory factor analysis, confirmatory factor analysis, and structural equations modelling. The sample consisted of 70 hotel managers and the instrument for data collection was a closed questionnaire. As the main results, it is noteworthy that of the 32 variables studied, 13 variables are connected to high performance in medium-sized hotels in Greater Florianópolis. The research confirmed the proposed model in which Strategic Human Resources Management is directly related to hotel performance. The study showed that employee training and development, as well as structuring the workplace, are essential Strategic Human Resources Management practices to obtain high performance.